Vegetation Structure and Environmental Correlates of Climbing Behavior for Desert Shrub Ochradenus baccatus - Dhafer A. Al-Bakre (Plants)
Ochradenus baccatus Delile (Resedaceae) is a widely distributed desert shrub known for its remarkable growth form plasticity, growing either independently or as a facultative climber on other vegetation. Despite its ecological adaptability, the drivers underlying its dual growth strategy remain poorly understood in arid ecosystems. This study aimed to investigate the growth form plasticity of O. baccatus across diverse ecological gradients in Saudi Arabia and identify key environmental and floristic factors influencing its climbing and independent forms. Field surveys were conducted from 2020 to 2024 across 103 sites, using stratified random sampling. At each site, vegetation data were collected using 50 × 50 m quadrats, and species composition, life form percentage, and O. baccatus behavior were recorded. Results revealed clear ecological separation between behaviors. Climbing individuals were associated with higher elevations, greater tree and shrub cover, and moderate soil fertility, while independent individuals were broadly distributed in herbaceous and open habitats. Diversity indices (Shannon, Simpson, evenness) increased with altitude, particularly in climbing habitats. PERMANOVA confirmed significant differences in species composition between behaviors (p = 0.0001), and SIMPER analysis identified species like Haloxylon salicornicum and Zygophyllum album as key contributors in climbing habitats. Indicator species analysis revealed behavior-specific taxa, while CCA demonstrated that rainfall, soil moisture, and temperature were the strongest environmental predictors of growth behavior. This study highlights the ecological flexibility of O. baccatus and the role of environmental filtering and plant community structure in shaping its growth strategy. These results have implications for the growth form plasticity of desert plants and can be applied to vegetation management and restoration in arid ecosystems.